Analisis Kondisi Isolator Outdoor Terpolusi Debu Urea dengan Metode PRPD dan Time Frequency - Gustian, Rindo; Firmansyah, Anton; Nurul Utami, Pertiwi (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the characteristics of partial discharge (PD) on a 13.8 kV Outdoor Station Post Insulator exposed to urea dust contamination at PT X Palembang. Urea dust deposited on the insulator surface increases surface conductivity and triggers PD activity that may lead to insulation degradation. Measurements were conducted using a Megger PD Scan device with a ultrasonic sensor, then processed in MATLAB to generate Phase Resolved Partial Discharge (PRPD) patterns and Time Frequency Partial Discharge (TFPD) analysis using STFT, FFT, and CWT methods. Results showed ultrasonic values of -5 dB to 4 dB, with the highest PD activity detected at Reactor P4. The PRPD pattern displayed symmetric pulse distribution across both half-cycles of the AC waveform at low intensity, indicating surface discharge due to surface contamination. TFPD analysis revealed a dominant frequency of 24.41 kHz. Overall, the insulation condition remains good and safe for operation, confirming that the combined PRPD and TFPD methods are effective for comprehensive insulator condition monitoring.